Diversity and biological traits of bees visiting flowers of Cucurbita maxima var. zapallito differ between biodiversity-based and conventional management practices - Dalmazzo, Maria de los Milagros; Zumoffen, Leticia; Ghiglione, Carla; Roig-Alsina, Arturo; Chacoff, Natacha Paola (Springer Nature, 2024)
Low diversity of pollinators and the modified composition of functional groups of bees have been proposed as the causes of pollination deficiency in cultivated Cucurbitaceae species. Functional groups of bees are determined by traits, such as body size, nesting site, and social behavior. The presence of bees with specific traits can be differentially affected by agricultural management practices. This work aimed to assess how management types (agroecological and conventional) in Cucurbita maxima var. zapallito crops affect the abundance of bees with different biological traits. The study was conducted on four farms located in horticultural areas of central-eastern Santa Fe province, Argentina. A total of 108 10-min censuses were conducted to record bee species abundance in flowers. The species were assigned to categories for each of the three biological traits. A total of 552 individuals, belonging to 16 bee species, were recorded. Honey bees were more abundant under conventional management, whereas the native bees Eucera fervens and other species were more abundant under agroecological management. Species of the categories analyzed (body size: small, medium, and large; nesting site: above-ground cavities or ground-nesting; and social behavior: solitary or social) were present on farms under both management types. We found that management type affected bees, and their effects differed among bees with specific biological traits. Medium-sized and small bees, ground-nesting bees, and solitary bees were found in greater abundance on agroecological farms than on conventional farms. Our data allowed us to explain the diversity and abundance of bees relative to the management type and biological traits of the species. Implications for insect conservation: This study suggests that incorporating biodiversity-based management strategies might increase abundance and richness of native bees with different biological traits, ensuring the free pollination service they provide and a taxonomically and functionally diverse assemblage.